2021
DOI: 10.1007/s00027-021-00832-5
|View full text |Cite
|
Sign up to set email alerts
|

Main macroinvertebrate community drivers and niche properties for characteristic species in urban/rural and lotic/lentic systems

Abstract: The effect of urbanization is often reflected both in lotic and lentic habitats, through changes in diversity and structural and compositional changes in macroinvertebrate communities. In this study, we focused on macroinvertebrate assemblage in lotic and lentic ecosystems of the Krąpiel River catchment area (NW Poland) with the following aims: (1) to determine the main driver in structuring lotic and lentic macroinvertebrate communities and the factors that influence them in urban versus rural landscapes; (2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Most water mite genera exhibited negative correlation with water parameters indicating sensitivity to pollution (Goldschmidt 2016;Savić et al 2022). Abelho et al (2021), who carried out an experiment on the effect of salinity on aquatic macroinvertebrates, also suggested that genera diversity and abundance are negatively correlated with salinity as it impacts on the osmoregulation of aquatic insects and often hypertonicity can be lethal (Griffith 2017)…”
Section: Authors Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most water mite genera exhibited negative correlation with water parameters indicating sensitivity to pollution (Goldschmidt 2016;Savić et al 2022). Abelho et al (2021), who carried out an experiment on the effect of salinity on aquatic macroinvertebrates, also suggested that genera diversity and abundance are negatively correlated with salinity as it impacts on the osmoregulation of aquatic insects and often hypertonicity can be lethal (Griffith 2017)…”
Section: Authors Contributionsmentioning
confidence: 99%
“…Water mite are greatly influenced by water parameters and environmental factors (Stryjecki et al 2016;Savić et al 2022). Abundance of water mites is negatively influenced by water temperature and velocity (Stryjecki et al 2018), with temperature being the major factor that influences distribution of Hydrachnidia along altitudinal gradients.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have already highlighted the importance of a wide range of pond types to provide heterogeneous habitats both in urban (Hassall et al 2016; Pinel-Alloul et al 2022) and rural (Biggs et al 2005réghino et al 2008a regions. Despite a generally lower local diversity than their rural counterparts (Savić et al 2022;Hassall and Anderson, 2015), urban waterbodies are also often more heterogeneous in abiotic conditions at the landscape scale, which could potentially lead to similar gamma diversity (Hill et al 2016). In that context, urban and rural ponds are considered as a model system in conservation, ecology and evolutionary biology (De Meester Approaches using both taxonomic and functional composition have been instrumental for identifying groups of taxa with uniform responses to environmental gradients, as well as keystone traits whose loss may lead to a rapid collapse of the ecosystem (McGill et al 2006;Baird et al 2008).…”
Section: Introductionmentioning
confidence: 98%